The Effect of a Perceptual-Motor Program Based on Johnstone and Ramon Method on Gross Motor Skills of Children With Visual Impairment: A Randomized Controlled Trial - Hooshang Mirzaie; Seyed Ali Hosseini; Abbas Riazi; Fatemeh Ghasemi Fard; Mehdi Jafari Oori; Samaneh Hossein Zadeh; Narges Hooshmand Zadeh (University of Social Welfare and Rehabilitation Sciences, 2020)
Objective: The integration of various senses with each other in the form of perceptual-motor activities can lead to the promotion of different aspects of physical, perceptual, cognitive, and psychosocial development. Decreased visual acuity in children with visual impairment makes it difficult to develop motor skills, including gross motor skills. A few studies have used perceptual-motor interventions in these children with no specific framework. The purpose of this study is to evaluate the effect of a perceptual-motor intervention based on Johnstone and Ramon's method on the gross motor skills of children with visual impairment. Materials & Methods: In this randomized controlled trial, the study population consisted of children aged 7-10 years with visual impairment (blind or with low vision) studying in three schools of Narjes (Girls' school), Shaid Mohebbi, and Shahid Khazaeli (Boys' schools) in Tehran City, Iran in 2018 (n=140). Of these children, 24 who had met inclusion criteria were selected and randomly assigned into two intervention (n=12) and control (n=12) groups. The perceptual-motor program was designed based on Johnstone and Ramon's method and validated by a panel of experts that included four members of the Department of Occupational Therapy, the University of Social Welfare and Rehabilitation Sciences, and one optometrist from the Baqiyatallah University of Medical Sciences. The intervention group received the perceptual-motor program for two months, three 45-min sessions per week (24 sessions in total). The gross motor skills of both groups were measured by the second edition of Movement Assessment Battery for Children (MABC-2) test (aiming/catching and balance subscales) and the second edition of Test of Gross Motor Development (TGMD-2) (locomotor and object control subscales) in three stages: Pre-test, post-test, and 1-month follow-up. Data analysis was performed using the Shapiro-Wilk test, Mann-Whitney U test, Friedman test, Bonferroni test, and generalized estimating equation in SPSS v. 22. The significance level was set at 0.05. Results: The mean±SD ages of children in the intervention and control groups were 9.2±1.1 and 8.3±1.2 years, respectively. The mean±SD scores of aiming/catching skill in the intervention group reached from 4.17±2.82 in the Pre-test phase to 11.17±1.95 in the post-test and 10.92±1.62 in the follow-up phases. In the control group, the mean±SD scores were 3.83±2.79 in the Pre-test, 4.25±3.08 in the post-test, and 4.67±2.93 in the follow-up. The mean±SD scores of the balance skill increased from 6.25±2.42 in the Pre-test to 10±2.13 in the post-test and 9.92±2.19 in the follow-up phase. In the control group, the scores were 3.50±3.09) in the Pre-test, 3.83±3.46) in the post-test, and 4±3.36) in the follow-up phase. The mean±SD score of the locomotor skill was 40.92±9.34 in the Pre-test, 47.58±1.17 in the post-test, and 47.42±1.08 in the follow-up phase. In the control group, these scores increased from 35.83±12.92 in the Pre-test to 36.83±13.17 and 37.67±13.24 in the post-test and follow-up phases, respectively. The mean±SD scores of object control skill increased from 32.50±14.74 in the Pre-test to 47.50±1.24 in the post-test and 47.66±1.15 in the follow-up, while in the control group, the scores were 29.25±12.93 in the Pre-test, and 30.17±12.89 and 30.08±13.34 in the post-test and follow-up phases. The aiming/catching, balance, and object control skills of children were significantly improved after the intervention (P<0.05), and continued after one month. In contrast, the locomotor skill was not improved after the intervention (P>0.05). Conclusion: The perceptual-motor interventional program can be useful in promoting the gross motor skills of children with visual impairment. It is suggested that this program be used in other studies on visually-impaired children.